Articulate Storyline Interactive Learning Media on the Topic of Plant Anatomy - Fatoni, Muhammad Rizal; Bektiningsih, Kurniana (Universitas Pendidikan Ganesha, 2024)
The lack of diversity in learning media used to support science and science learning and the lack of innovative media, especially IT-based media, result in students' low understanding of the material. This research aims to develop interactive learning media based on Articulate Storyline to improve students' understanding. This type of research is development (Research and Development) with the Borg and Gall research model. Data collection methods use observation, interviews, and questionnaires. The data collection instrument uses a questionnaire sheet. Testing product designs is conducted by material experts, media experts, and students. Experts provide a feasibility test assessment of the media, while some students will conduct small-scale trials. The analysis techniques used are qualitative and quantitative. The research results showed that the assessment of material experts was 88.7%, and the assessment of media experts was 85%. The results of the N-Gain test assessment obtained a score of 0.58. It was concluded that interactive learning media based on Articulate Storylines is feasible and effective in improving the learning outcomes of fourth-grade elementary school students.